Thirsty cities: the urban water footprint and the peri-urban interface, a four city case study from West Africa - Drechsel, Pay; Cofie, Olufunke O.; Amoah, Philip (2014)
Urbanisation is increasingly affecting inter-sectoral water allocations. This paper looks beyond physical water transfers at the larger urban water footprint and how much it is affecting the urban periphery in the case of four cities in West Africa (Accra, Kumasi, Tamale and Ouagadougou). The results showed a water footprint variation between 892 and 1,280 m3/capita/year for these four cities based on actual and virtual water flows. The virtual flow through the food chain is outscoring actual domestic water consumption by a factor of 40–60 and using water resources far beyond the peri-urban interphase. However, the picture is changing with consideration of the grey water footprint. Due to limited wastewater treatment, peri-urban areas are the hot spots of water pollution diminishing their fresh water resources. The fresh water affected by the urban return flow easily doubles the overall urban water footprint. Improved on-site sanitation, especially with water saving and urine and excreta separating toilets would have a significant positive impact on the quality and quantity of the urban water footprint given that actual water availability is limiting large scale sewer connections for final wastewater treatment.